Gender egalitarianism in the household during the Covid-19 pandemic: A case study of male spousal support in Jabodetabek - Zulfah Azrah; Maria Jacinta Arquisola (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This research aims to analyze how the male spouses perceive gender equality and support the work-life balance of their female working spouses during the Covid- 19 pandemic. This research uses a descriptive qualitative research method with a data collection method is an interview. The data from this study was collected from 13 male spouse interviewees whose wives work, have at least one child, and are domicile in Jabodetabek. Based on the research results, it can be concluded that (1) Gender equality occurs in households from access, control, participation, and benefit has been realized in the interviewees’ household life. (2) Factors such as financial factors, spousal support, and work pressure affect the work-life balance of female working spouses during the Covid-19 pandemic. The results of this study can be used for male spousal to improve the perception of gender equality in the household from several aspects such as access, control, participation, benefit, and supporting work-life balance of female working spouses by paying attention to several aspects such as time balance, involvement balance, and satisfaction balance to achieve a work-life balance of the female working spouses.